Pendidikan Moral melalui Pembelajaran Kitab Al-AkhlÄq li Al-BanÄ«n - A'yunin, Qurrotu; Muhid, Abdul (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2022)
Islamic education basically contains a lot of moral values in the scope of its study, because Islam has come to bring some moral guidelines which are reflected in the words and actions of the Prophet Muhammad SAW. This study aims to examine moral education through the study of the book al-AkhlÄq li al-BanÄ«n by Sheikh Umar Baraja. This study uses a qualitative method with the type of library research. Researcher analyzed written literature as the main source in the form of classic books, books, research journals, and other publication media. Based on this literature review, it shows that moral education through learning the book of al-AkhlÄq li al-BanÄ«n adds character education innovation in the midst of today's moral decadence. Learning the book of al-AkhlÄq li al-BanÄ«n must be accompanied by other methods of moral internalization to achieve maximum results.